Does Market Competition Lead to Customization? - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2014)
This paper proposes a theory of competition and customization. When firms allocate their production to both custom-made and standardized products, the fraction of sales from the former will increase in the face of increased competition. Recent surveys conducted by the World Bank on Chinese firms provide a rare direct measure of customization that allows us to test the above-mentioned prediction. We find empirical results consistent with the prediction.